Cryptococcal Osteomyelitis of the Left Acetabulum: A Case Report - Zhou, Changning; Zhang, Jing; Chen, Yang; Ding, Xing; Chen, Fen; Feng, Kai; Chen, Kuntao (Current Medical Imaging, 2023)
Background: Cryptococcus, as a classical
Keywords: case report